ANALISIS PUTUSAN SELA TERHADAP PERMOHONAN PEMBAYARAN UPAH PROSES DALAM PENGADILAN HUBUNGAN INDUSTRIAL (STUDI PUTUSAN: PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL NOMOR: 181/PDT.SUS-PHI/2016/PN.BDG jo PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL NOMOR: 82/PDT.SUS-PHI/2016/PN.BDG) - Yolanda Pracelia; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2019)
Based on Article 96 of Law No. 2 of 2004 concerning Industrial Relations Dispute Settlement states that in essence that if the Company is proven at the first session not to carry out its obligations under Article 155 Paragraph (3) Law No. 13 of 2003 concerning Manpower, the Judge may decide interim. In the Decision of the Industrial Relations Court Number: 181/Pdt.Sus-PHI/2016/PN.Bdg jo Decision of the Industrial Relations Court Number: 82/Pdt.Sus-PHI/2016/PN.Bdg, the Judge decides on the request for payment of process wages at interlocutory decisions and final decisions, thus raising problems, how is the legal certainty of the application for process wage payments in the Industrial Relations Court and how to prove in the request for payment of process wages in the Industrial Relations Court. This study uses normative legal research methods, which are prescriptive in nature, with methods of data collection in the form of library studies, and supported by the results of interviews with Labor Law Experts. The results of the study show that, first, legal certainty in the request for payment of process wages on interlocutory decisions must be logical and not cause doubt. Second, the evidence applied at the time of the Industrial Relations Dispute is not in accordance with the situation that occurred in practice, so that it burdens the Workers. In the decision of the Industrial Relations Court Number: 181/Pdt.Sus-PHI/2016/PN.Bdg jo Industrial Relations Decision Number: 82/Pdt.Sus-PHI/2016/PN.Bdg is not in accordance with the Laws and Regulations in Indonesia.